Love like sky - Youngblood, Leslie C. (Disney Hyperion, 2018)
Eleven-year-old Georgie is still adjusting to leaving Atlanta for a small town, having a stepfather, and being unable to get close to her stepsister when her six-year-old sister, Peaches, suddenly becomes very ill.